Clinical features analysis for complications in infants with late-onset Group B streptococcal sepsis: a retrospective case-control study - Geng, Haifeng; Sun, Wenqiang; Shen, Qiuping; Li, Cancan; Li, Wenmei; Wang, Huawei; Wu, Zhixin; Zhu, Xueping (Frontiers in Medicine, 2025)
ObjectiveTo investigate the risk factors associated with complications in infants with late-onset Group B Streptococcal (GBS) sepsis, and to provide evidence for clinical intervention strategies.MethodsThis study is a retrospective case-control study. The clinical data of 101 infants with late-onset GBS sepsis, diagnosed before 3 months of age were retrospectively analyzed. According to the presence or absence of complications, the infants were divided into the complication group and the non-complication group. Univariate and multivariate analyses were performed to explore the risk factors associated with the occurrence of complications in infants with late-onset GBS sepsis. Using ROC curves to evaluate the predictive efficacy of clinical variables.ResultsA total of 101 cases of late-onset GBS sepsis met the inclusion criteria, including 41 in the non-complication group and 60 in the complication group. The gestational age in the complication group was significantly lower than that in the non-complication group (P < 0.05). Clinically, the complication group had a higher incidence of seizure, bulging anterior fontanelle, and fever, as well as a significantly lower PaO2/FiO2 ratio (P < 0.05). Laboratory findings showed that the complication group had a higher incidence of hypoalbuminemia, concomitant positivity in blood and cerebrospinal fluid cultures, elevated creatinine and blood urea nitrogen levels, and significantly lower pH and albumin levels (P < 0.05). In addition, the complication group exhibited significantly higher Pediatric Sequential Organ Failure Assessment (pSOFA) scores, Pediatric Logistic Organ Dysfunction Score 2 (PELOD-2) scores, and higher proportion of patients with high pSOFA (>3.50) and PELOD-2 scores (>3.50) (P < 0.05). Multivariate analysis revealed that high PELOD-2 score, high pSOFA score, high creatinine levels and hypoalbuminemia were risk factors for the development of complications in infants with late-onset GBS sepsis; the ROC curve constructed using these predictors demonstrated excellent discriminative ability, with an AUC of 0.858 (95% CI: 0.782–0.934), sensitivity of 77.78%, and specificity of 82.61%.ConclusionHigh PELOD-2 score, high pSOFA score, high creatinine levels, and hypoalbuminemia independently predict complications in late-onset GBS sepsis infants, enabling early risk stratification and tailored treatment to improve outcomes.